CABE-RY: A PAM-flexible dual-mutation base editor for reliable modeling of multi-nucleotide variants - Wanyu Tao; Qing Liu; Shisheng Huang; Xin Wang; Shiyuan Qu; Junfan Guo; Danfeng Ou; Guanglei Li; Yu Zhang; Xiangmin Xu; Xingxu Huang (Elsevier, 2021)
Multi-nucleotide variants (MNVs) represent an important type of genetic variation and have biological and clinical significance. To simulate MNVs, we designed four dual-mutation base editors combining hA3A(Y130F), TadA8e(V106W), and protospacer adjacent motif (PAM)-flexible SpRY and selected cytosine and adenine base editor-SpRY (CABE-RY), which had the best editing performance, for further study. Characterization and comparison showed that CABE-RY had a smaller DNA editing window and lower RNA off-target edits than the corresponding single base editors. Thus, we have established a versatile tool to efficiently simulate MNVs over the genome, which could be very useful for functional studies on MNVs in humans.